Solubility of atenolol in ethanol+ water mixtures at various temperatures - Hamidi Samin; Jouyban Abolghasem (Journal of the Serbian Chemical Society, 2015)
The experimental solubility of atenolol in ethanol + water mixtures at different temperatures (298.2, 303.2, 308.2 and 313.2 K) was reported. The solubility was calculated with five numerical methods; i.e., the Jouyban-Acree model (method I), its combination with van’t Hoff equation (method II), the extended version of the Jouyban-Acree model with Abraham parameters (method III), the minimum number of data points (N) were used to train the Jouyban-Acree model (N=11) and its combination with van’t Hoff equation (N=22), then obtained parameters of the models were used to calculate the solubilites at other temperatures (methods IV and V). The accuracies of the calculated solubilites were evaluated by computing mean percentage deviation (MPD). The obtained MPDs (± standard deviation) for methods I, II, III, IV and V were 5.6±7.1, 5.1±4.6, 34.1±28.0, 10.0±9.6 and 6.6±4.8%, respectively.